Dobutamine Stress Echocardiography Safety in Chagas Disease Patients - Rassi,Daniela do Carmo (2017)
Abstract Background: A few decades ago, patients with Chagas disease were predominantly rural workers, with a low risk profile for obstructive coronary artery disease (CAD). As urbanization has increased, they became exposed to the same risk factors for CAD of uninfected individuals. Dobutamine stress echocardiography (DSE) has proven to be an important tool in CAD diagnosis. Despite being a potentially arrhythmogenic method, it is safe for coronary patients without Chagas disease. For Chagas disease patients, however, the indication of DSE in clinical practice is uncertain, because of the arrhythmogenic potential of that heart disease. Objectives: To assess DSE safety in Chagas disease patients with clinical suspicion of CAD, as well as the incidence of arrhythmias and adverse events during the exam. Methods: Retrospective analysis of a database of patients referred for DSE from May/2012 to February/2015. This study assessed 205 consecutive patients with Chagas disease suspected of having CAD. All of them had their serology for Chagas disease confirmed. Results: Their mean age was 64±10 years and most patients were females (65.4%). No patient had significant adverse events, such as acute myocardial infarction, ventricular fibrillation, asystole, stroke, cardiac rupture and death. Regarding arrhythmias, ventricular extrasystoles occurred in 48% of patients, and non-sustained ventricular tachycardia in 7.3%. Conclusion: DSE proved to be safe in this population of Chagas disease patients, in which no potentially life-threatening outcome was found.